1999
DOI: 10.1093/nar/27.16.3371
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from CD spectra and melting temperatures for stable Hoogsteen-paired oligomer duplexes derived from DNA and hybrid triplexes

Abstract: The pyr*pur.pyr type of nucleic acid triplex has a purine strand that is Hoogsteen-paired with a parallel pyrimidine strand (pyr*pur pair) and that is Watson-Crick-paired with an antiparallel pyrimidine strand (pur.pyr pair). In most cases, the Watson-Crick pair is more stable than the Hoogsteen pair, although stable formation of DNA Hoogsteen-paired duplexes has been reported. Using oligomer triplexes of repeating d(AG)12 and d(CT)12 or r(CU)12 sequences that were 24 nt long, we found that hybrid RNA*DNA as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
(85 reference statements)
3
18
1
Order By: Relevance
“…As expected, the triplex with RNA as third strand is of higher thermal stability than that with DNA 18. 20…”
Section: Resultssupporting
confidence: 68%
“…As expected, the triplex with RNA as third strand is of higher thermal stability than that with DNA 18. 20…”
Section: Resultssupporting
confidence: 68%
“…Moreover, the shift in peak position does not take place at ∼218 and ∼282 nm (see the Supporting Information). This implies that the triplex would be formed by a one-step docking under acidic conditions (55). At high pH, the CD spectra have no negative peak at ∼218 nm and present a typical characteristic of Watson-Crick duplex formation along with the temperature change (see the Supporting Information), which suggests that the triplex is not formed under this condition.…”
Section: Eigenpeak Of the CD Spectra For The Hoogsteen Pairedmentioning
confidence: 95%
“…16 The behavior of more complicated systems such as a DNA-RNA hybrid duplex and triplex is also scrutinized. 17,18 It is interesting that the CD showed that the homodimers, as well as single stranded DNA, also form a helical structure through base stacking. 12 Because deformation of the helical structure will change the shape of the CD spectrum, the reduction of the value and shift of the peak clearly indicate the degree of structural reorientation of dC 10 .…”
Section: Probing Molecular Change With CDmentioning
confidence: 99%